Pengembangan Manajenen Keuangan/Pembiayaan di Sekolah - Fanandi, Ardian Tri (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Lampung, 2023)
Financial management is one of the elements of school management which will also determine the running of educational activities in schools in efforts to achieve, control and ensure goals are met. This article aims to analyze the financial management of educational institutions/schools. The production of this article uses qualitative methods as a strategy to collect and utilize all information related to the issues discussed from various journal sources on the internet. From the research that has been done, the management of financial management and financing can work well by means of planning, organizing, implementing and supervising. creative and effective from the principal and all parties involved.